Pembuatan Label sebagai Media Komunikasi pada Koleksi Peristiwa Operasi Trisula di Museum Brawijaya - Fatmasari, Ardha; Farika Nikmah (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Museums as cultural preservation institutions have the responsibility to convey information about collections in an informative manner to the public. One of the historical events displayed at the Brawijaya Museum is Operation Trident in 1968. This research aims to design collection labels as an effective communication medium by considering aspects of archive classification, material selection, label design, and information readability. The method used is action research which is carried out through the planning and action stages. The label is designed using Art Paper material with a combination of black-and-white colors and Times New Roman fonts. This research not only emphasizes the aesthetic aspect, but also pays attention to the functional aspect in conveying messages to visitors. The label design process is carried out by paying attention to the suitability between historical content and the form of visual presentation, so that information can be conveyed in a concise, clear, and interesting manner. Effectiveness evaluation was carried out through the EPIC model approach to 105 respondents, including empathy, persuasion, impact, and communication indicators. The results of the study showed that the label was designed to be very effective as a communication medium for museums with high scores on all four indicators. The implication of this research is to improve the visitor experience in understanding the historical value of collections and the efficiency of archive management in the museum environment. In addition, the design of this label can be a reference for other museums in developing information media based on a visual communication approach that is right on target. Thus, the museum serves not only as a repository of artifacts, but also as an interactive and communicative educational center. Furthermore, this research emphasizes the importance of integration between information technology and visual communication strategies in the management of modern museums. The use of professionally designed labels based on the results of empirical evaluation contributes to the improvement of the image of museum institutions in the eyes of the public. It is hoped that this approach can encourage museums to be more innovative in creating participatory learning experiences, especially for the younger generation.